Mapping the profiles of franchisees: getting to know the black sheep, rough diamonds, whingers and best buddies - Huang, Y.; Phau, Ian (Emerald Group Publishing Limited, 2009)
The purpose of this paper is to investigate franchisees' perception of the value of quality service in the franchise system. Two dimensions, perceived importance and perceived gaps of the quality of the franchise system, form the anchors of a proposed 2 x 2 franchise system quality(FSQ) matrix. This is empirically tested with 200 Australian franchisees. The results reflected a strong evidence of four distinct profiles of franchisees as conceptualized. These results also showed that the more cooperative the franchisees, the better their performance and satisfaction levels with the system. In contrast to existing literature, franchisees who fall in the high-perceived importance cells of the FSQ matrix have a stronger desire for autonomy. Cooperation between franchisees and franchisors are fundamental to achieve success. It is important to provide resources and assistance to franchisees and these are considered as key success factors. Further, determining the profile of the franchisees allows franchisors to determine the potential Best Buddy who are considered an asset in the franchise system. A larger sample size should be implored that focuses on specific industries or service sectors. The research can be replicated in other non-Western contexts to formulate different insights. Cross-national studies could be conducted to investigate differences between cultures. The paper addresses the gap in literature by examining franchisees? perception of the value of services provided in a franchise system. The FSQ Matrix is also conceptualized and empirically tested on an Australian sample.